Prematurity-Related Hypertension in Children and Adolescents - Karolina Poplawska; Karolina Dudek; Maja Koziarz; Dominik Cieniawski; Tomasz Drozdz; Sylwester Smialek; Dorota Drozdz; Przemko Kwinta (International Journal of Pediatrics)
Due to the functional and structural immaturity of different organ systems, preterms have a higher rate of morbidity and mortality. The prevention and treatment of the complications of prematurity is a major challenge in perinatal health care. Recently, there have been several multicenter research trials analysing the impact of prematurity or low birth weight on the health problems of children and adolescents. Many of these studies deal with the issue of pediatric hypertension. An analysis of 15 studies conducted in the years 1998–2011, in which blood pressure values in ex-preterm children were measured, was performed. Comparison was based on several issues: measurement method, cohorts age, size, and birthweight. It has been proven that hypertension occurs more often in former preterm infants; however the etiologic pathways that cause this condition still remain unclear. Moreover, pediatric hypertension is a significant problem, because of its transformation into adult hypertension and increased cardiovascular risk later in life. Therefore it is crucial to introduce wide-spread screening and detection of elevated blood pressure, especially among prematurely born children.